TET3 regulates DNA hydroxymethylation of neuroprotective genes following focal ischemia - Morris-Blanco, Kahlilia C (J Cereb Blood Flow Metab, 2020)
The 5-hydroxymethylcytosine (5hmC) epigenetic modification is highly enriched in the CNS and a critical modulator of neuronal function and development. We found that cortical 5hmC was enhanced from 5 min to three days of reperfusion following focal ischemia in adult mice. Blockade of the 5hmC-producing enzyme ten-eleven translocase 3 (TET3) increased edema, infarct volume, and motor function impairments. To determine the mechanism by which TET3 provides ischemic neuroprotection, we assessed the genomic regions where TET3 modulates 5hmC. Genome-wide sequencing analysis of differentially hydroxymethylated regions (DhMRs) revealed that focal ischemia robustly increased 5hmC at the promoters of thousands of genes in a TET3-dependent manner. TET3 inhibition reduced 5hmC at the promoters of neuroprotective genes involved in cell survival, angiogenesis, neurogenesis, antioxidant defense, DNA repair, and metabolism demonstrating a role for TET3 in endogenous protection against stroke. The mRNA expression of several genes with known involvement in ischemic neuroprotection were also reduced with TET3 knockdown in both male and female mice, establishing a correlation between decreased promoter 5hmC levels and decreased gene expression. Collectively, our results indicate that TET3 globally increases 5hmC at regulatory regions and overwhelmingly modulates 5hmC in several neuroprotective pathways that may improve outcome after ischemic injury.